159 The Need Of Six Monthly Follow Up X-Rays Post Total Knee Replacement(TKR). (12th October 2021) - Baig, N; Ferrari, M; Lukaszewicz, A
Abstract: Background: There is a longstanding culture of repeat x-rays after total knee replacement (TKR) as part of follow up, often combined with a clinic review. This is to check that the prosthesis is in a satisfactory position. There are inherently a number of issues with this historic approach including exposure of patients to further radiation who may be asymptomatic, time delays in busy clinics or x-ray departments and costs. Objectives: The aim of this audit was to assess whether follow up plain films after TKR are methodically undertaken and of benefit to confirm satisfactory appearance if immediate post -operative x-rays were unremarkable. The findings of a six month follow up x-ray was specifically evaluated. The secondary aim was to establish the timing of further follow up x-rays within the department. Method: 200 patients were included within the analysis, they all received a TKR at a major trauma centre, over a one-year period between December 2017 and December 2018. Results: It was found that 100% of those patients having a post-operative film had a satisfactory appearance. 78% of patients had at least one further follow op x-ray of which 99.4% were satisfactory. Up to five follow up x-rays were taken with 53.5% of patients having a follow up x-ray at 6 months. Conclusions: From the above results there is minimal, if any, evidence within the data set to support routine, additional follow up imaging if initial post-operative films are satisfactory, and the patient is asymptomatic.